Bioethanol production through dilute sulfuric acid hydrolysis and yeast fermentation of Sugrcane bagase. - Oppus, Dia Monica
In this study, sugarcane bagasse was subjected to a 24-h pretreatment using 10 percent (v/v) NH4OH in a liquid to solid ratio of 100 mL/gram of sugar bagasse. The pretreated bagasse were then subjected to dilute sulfuric acid hydrolysis with using 0.4 -0.7 percent (v/v) as the final sulfuric acid concentration. The amount of total sugar in the hydrolysates was measured using the anthrone method. The 0.7 percent sulfuric acid treatment gave the highest total yield of 0.49 mg/mL. The effects of pH on the fermentation of the hydrolysates were also studied by adjusting the pH to 4.5, 5.0, 5.5 and 6.0. Simple distillation was performed to extract the ethanol from the mixture. Quantification and characterization of ethanol distillate was done using a refractometer and infrared spectrometer, respectively. The highest alcohol concentration obtained was 4.26 percent (v/v) ethanol from the 4.5 treatment. One-way analysis of variance (ANOVA) at 95 percent confidence interval revealed a significant difference among the amounts of sugar and alcohol obtained.